Cloherty and stark's manual of neonatal care - Eichenwald, Eric C.; Hansen, Anne R.; Stark, Ann R.; Martin, Camilia R. (Wolters kluwer, 2017)
he Eighth Edition of Cloherty and Stark's Manual of Neonatal Care maintains that tradition of excellence, offering NICU physicians, neonatal-perinatal fellows, residents, and neonatal nurse practitioners quick access to key clinical information, fully updated to reflect recent advances in the field. Written in an easy-access outline format, this extensively revised edition covers current, practical approaches to the evaluation and management of routine and complex conditions encountered in the fetus and the newborn.